Hypothalamic proopiomelanocortin neurons are glucose responsive and express K ATP channels - Ibrahim, Nurhadi (2003)
Hypothalamic proopiomelanocortin (POMC) neurons are critical for controlling homeostatic functions in the mammal. We used a transgenic mouse model in which the POMC neurons were labeled with enhanced green fluorescent protein to perform visualized, whole-cell patch recordings from prepubertal female hypothalamic slices. The mouse POMC-enhanced green fluorescent protein neurons expressed the same endogenous conductances (a transient outward K + current and a hyperpolarization-activated, cation current) that have been described for guinea pig POMC neurons. In addition, the selective μ-opioid receptor agonist DAMGO induced an outward current (maximum of 12.8 ± 1.2 pA), which reversed at K + equilibrium potential (E K+ ), in the majority (85%) of POMC neurons with an EC 50 of 102 nM. This response was blocked by the opioid receptor antagonist naloxone with an inhibition constant of 3.1 nM. In addition, the γ-aminobutyric acid B receptor agonist baclofen (40 μM) caused an outward current (21.6 ± 4.0 pA) that reversed at E K+ in these same neurons. The ATP-sensitive potassium channel opener diazoxide also induced an outward K + current (maximum of 18.7 ± 2.2 pA) in the majority (92%) of POMC neurons with an EC 50 of 61 μM. The response to diazoxide was blocked by the sulfonylurea tolbutamide, indicating that the POMC neurons express both Kir6.2 and sulfonylurea receptor 1 channel subunits, which was verified using single cell RT-PCR. This pharmacological and molecular profile suggested that POMC neurons might be sensitive to metabolic inhibition, and indeed, we found that their firing rate varied with changes in glucose concentrations. Therefore, it appears that POMC neurons may function as an integrator of metabolic cues and synaptic input for controlling homeostasis in the mammal.